Antithrombotic Activity of Dermatan Sulphates, Heparins and their Combination in an Animal Model of Arterial Thrombosis - Iacoviello, Licia; D'Adamo, Maria Cristina; Pawlak, Krystyna; Polishchuck, Roman; Wollny, Tomasz; Buczko, Wlodzimierz; Donati, Maria Benedetta (Thrombosis and Haemostasis, 1996)
Dermatan sulphates have been shown to inhibit thrombus formation and thrombus growth in different experimental models of venous thrombosis. At variance with heparins, they show a remarkably low haemorrhagic potential. On the other hand, very few data are available on the effect of dermatan sulphates on arterial thrombus formation. We evaluated the effects of a low molecular weight (LMW)-dermatan sulphate, a high molecular weight (HMW)-dermatan sulphate and sulo-dexide (a mixture of fast-moving heparin fraction and dermatan sulphate) in comparison with LMW- and HMW-heparin, in a model of arterial thrombosis in rats. The insertion of an artificial prosthesis into the abdominal aorta of the animals induced the formation of an occluding thrombus within 2-5 days. The time in which 50% of the loops became occluded (OT50) was also calculated and used to compare the efficacy of the different drug treatments. This was 2.84 days for control animals and 4.25 and 5.80 days for HMW- and LMW-dermatan sulphate, respectively. Neither drug changed the “template” bleeding time, even at higher doses. In contrast, HMW-heparin at doses (8 mg/kg, sc, twice a day) inducing an antithrombotic activity comparable to that of dermatan sulphates, dramatically prolonged the bleeding time. LMW-heparin at the same doses was ineffective. Sulodexide (10 mg/Kg, sc, twice a day) prolonged the occlusion time to the same extent as HMW-heparin (OT50 5.10 vs. 4.14 days), with less an effect on the bleeding time (144 ± 6 s vs. >300 s, respectively). Histological examination confirms that the prolongation of occlusion time induced by the drugs is really related to thrombus formation inhibition at the site of arterial wall injury.Acetyl salicylic acid (ASA) (100 mg/kg/day in drinking water as lysine acetylsalicylate) did not modify the effect of Desmin 370 and Sulodexide on both occlusion and bleeding time. However, while it did not increase the antithrombotic activity of HMW-heparin, it significantly prolonged its haemorrhagic effect. In conclusion, dermatan sulphates are effective inhibitors of arterial thrombosis in rats, without inducing bleeding complications.